Impact of the Crisis on Foreign Tourists in Phuket Province - ศรีธรรมราช สุมาลี; ถาวรประสิทธิ์ บุษกร (Parichart Journal, 2017)
This research aims to study the impact level of the crisis on foreign tourists and the factors related on the impact level of the crisis on foreign tourists in Phuket province. The data were collected from 400 foreign tourists. The study employed frequency, percentage, standard deviation, Likert and Ordinal Logistic Regression (OLR) for analysis. The results found that the aspect of politics/ life and property safety was a high level of impact. The aspects of economy and natural disaster were a moderate level. The factors related on the impact level of the economy side were education level of lower the secondary school, high school, diploma and bachelor, status of single and marriage, and European birthplace. The disaster was entrepreneurs and Oceanian birthplace. Finally the politic crisis, there were entrepreneurs, single status and countries in Europe